High-resolution CT predictors of hypersensitivity pneumonitis - Rival, Gilles; Manzoni, Philippe; Lacasse, Yves; Polio, Jean Charles; Westeel, Virginie; Dubiez, André; Soumagne, Thibaud; Laurent, François; Dalphin, Jean Charles (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: The purpose of this study was to evaluate the use of high-resolution chest computed tomography (HRCT) to distinguish hypersensitivity pneumonitis (HP) from other diffuse parenchymal lung diseases (DPLDs). Methods: We examined 130 consecutive patients admitted to our hospital with DPLDs proved by HRCT. Patients underwent clinical and paraclinical examinations. Two readers interpreted 111 HRCT scans using predefined criteria. Results: The findings in patients with HP were compared to those with other DPLDs (non-HP) by univariate and multivariate analyses. Five independent radiological predictors were identified and were given a weight according to their regression coefficient: ground-glass attenuation nodules (4 points), homogeneous ground-glass opacity (3 points), patchy ground-glass opacity (2 points), absence of adenopathy (2 points), and absence of linear/reticular patterns (2 points). A total score (that we called “diagnostic index”) of 5 offered the best trade-off between sensitivity and specificity. At this point of the ROC curve, the sensitivity, specificity, and likelihood ratio were 74%, 90% and 7.7, respectively. Given a pre-test probability of HP of 34% (i.e., 38 HP / 111 patients), the post-test probability was 79%. Conclusion: Our results provide evidence that HRCT can accurately distinguish HP from other DPLDs.